Philological and historical commentary on Ammianus Marcellinus XXVI - Boeft, J. den (Jan), 1935-2019 (Philological and Historical Commentary on Ammianus Marcellinus ;, 2008)
Continuing the series of philological and historical commentaries on Ammianus' Res Gestae, this volume deals with Book 26, in which the beginning of the reign of Valentinian and Valens is described and the rise and fall of the usurper Procopius.